Socioeconomic condition and dietary habits in relation to oral health in 12-year-old children from Sarajevo, Bosnia-Hercegovina - Zukanović, Amila; Nakaš, Enita; Marković, Nina; Arslanagić, Amra (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2018)
Introduction: Living conditions and socioeconomic status are the significant determinants of oral health. The research goal was toanalyze the dietary habits of 12-year-old children in Sarajevo, Bosnia-Hercegovina. Another goal was to investigate the differences infood cariogenicity of children living under different socioeconomic conditions and to determine their relationship with the oral health.Materials and methods: The sample included 109 children, classified in groups of high, average and low socioeconomic status. Basedon the survey and examination, data on nutrition and caries experience (DMFT index) were obtained.Results: There was a difference in dietary habits between children living under different conditions. Children of high socioeconomicstatus (SES) had a more favorable number of daily meals comparing to children of low socioeconomic status. The average DMFTindex, as a measure of caries experience of 12-year-old children amounted 4.8(±3.2). Children of high socioeconomic status hadsignificantly lower caries experience than those from average and low statuses (high SES DMFT 3,60±2,84SD vs. middle SESDMFT 5,28±3,83SD and low SES DMFT 5,47±2,53SD; p